Employee Retention Strategies: A Mediation Analysis of Job Satisfaction - Aristiani, Rindy; Nasution, Yasmine (Journal La Sociale, 2026)
This study examines the organizational determinants of employee job satisfaction and their effect on intention to stay within G Group, a diversified property and lifestyle business experiencing persistent turnover. A quantitative method was applied using Partial Least Squares Structural Equation Modelling (PLS-SEM). Survey data were collected from 244 employees with a minimum of three months’ tenure, ensuring relevance beyond probationary stages. Job satisfaction was positioned as a mediating variable. Organizational culture, compensation, and career development have a significant effect on job satisfaction, whereas work–life balance shows no significant influence on either job satisfaction or intention to stay. Job satisfaction strongly predicts intention to stay and mediates the effects of culture, compensation, and career development. The weaker influence of career development and work–life balance appears to be related to demographic characteristics and variations in respondents’ work experiences. The findings support Herzberg’s distinction between motivators and hygiene factors, while Social Exchange Theory clarifies how supportive culture and fair compensation generate reciprocal commitment, also align with Talent Management Theory that development practices influence retention mainly through their impact on satisfaction. Findings suggest that proactive strategies, such as strengthening supportive organizational culture, ensuring fair and transparent compensation, and building structured career development, are more effective in reducing turnover and improving employee intention to stay than reactive approaches like counteroffers or short-term retention responses. This study offers empirical insight into how retention mechanisms function across different business sectors within one organization, highlighting variations in employee perceptions shaped by distinct operational contexts.